Promotion Of Health Knowledge And Attitude Of Mother's Attitude In Providing MP-ASI Ages 6-24 Months - Ni Ketut Kariani; Armenia Eka Putriana (Politeknik Karya Persada Muna, 2022)
Backgroun : Provision of Supplementary Food is one of the important components of the Family Nutrition Improvement Business (UPGK) and a program designed by the government. In 2019, the prevalence of the nutritional status of children under five in Central Sulawesi Province with underweight problems was 11.3% of the RPJMN target of 17%, stunting was 21.4% of the RPJMN target of 28% and wasting of toddlers was 9.6% of the RPJMN target of 9.5%. Methods: The type of research used is quantitative research with a pre-experimental research design using a one group pre-test-post-test design. This research was carried out in Tondo Village, the activity was carried out on May 11, 2022. The population in this study were all mothers who had toddlers aged 6-24 months in Tondo Village, totaling 20 people. The sample of all mothers who have toddlers aged 6-24 months is as many as 20 people. The sampling technique in this study is the total sampling of this study using the Wilcoxon test or T test. Results: The results of statistical tests showed that the P-Value value of 0.000 had a significant effect on the average knowledge before health promotion of complementary feeding for infants aged 6-24 months. The results of the statistical test showed that the P-Value value of 0.000 had a significant effect on the average attitude after health promotion of complementary feeding for infants aged 6-24 months. Conclusion: There is an effect of health promotion on mother's knowledge and attitude in giving complementary feeding to infants aged 6-24 months with P-Value 0.000<0.05 in Tondo Village. Keywords: Health Promotion, Knowledge, Attitude, Complementary Foods for infants aged 6-24 months